Effect of Conscientiousness and COVID-19-Induced Job Stress on Organizational Citizenship Behavior Among Healthcare Professionals - Shayista Majeed; Sabiya Mufti; Sabzar Ahmad Peerzadah; Nazir Ahmed Nazir (Changing Societies & Personalities)
Drawing upon the tenets of trait activation theory, the present study aimed to explore the moderating effect of COVID-19-induced job stress on the association between conscientiousness and organizational citizenship behavior (OCB) among healthcare professionals. Data for the study were collected from 379 healthcare professionals in India through a systematic random sampling technique. The results revealed a positive impact of conscientiousness on OCB. Moreover, COVID-19-induced stress negatively moderated the relationship between conscientiousness and OCB. The study findings have, thus, contributed to the budding research stream on the consequences of global pandemics on social institutions and individuals in general and extended the validity of trait activation theory assumptions in particular. The study provides valuable practical insights that may assist authorities in devising policies that could help encourage employees to display more of these pro-social behaviors in times of natural calamities when such behaviors are of utmost necessity.